Porphyrin biosynthesis in the soybean callus tissue system-XVIII. Levels of succinyl coa synthetase, cysthationase, rhodanese, aminolevulinate synthetase and aminolevulinate dehydratase in clones of different age - Vazquez, E. (1980)
1. 1. The activity of Succinyl CoA Synthetase (Suc CoA-S), Cysthationase, Rhodanese, Aminolevulinate Synthetase (ALA-S) and Aminolevulinate Dehydratase (ALA-D) was studied in old (405-407 subcultures) and young (34-36 subcultures) soybean callus clones as a function of the days of growing. 2. 2. Suc CoA-S, ALA-S and ALA-D activities were much lower in old than in young callus, while the activity of Cysthationase and Rhodanese was higher in old callus. 3. 3. ALA-S reached its maximum activity when Rhodanese and Cysthationase their minimum, on the 11th day of growth. It is suggested that the cellular content of a possible thio-compound which would regulate ALA-S activity, is controlled through its degradation by Rhodanese. © 1980.